Immunogenicity and efficacy comparison of MDCK cell-based and egg-based live attenuated influenza vaccines of H5 and H7 subtypes in ferrets. Issue 40 (11th September 2020) - Yeolekar, Leena R.; Guilfoyle, Kate; Ganguly, Milan; Tyagi, Parikshit; Stittelaar, Koert J.; van Amerongen, Geert; Dhere, Rajeev M.; BerlandaScorza, Francesco; Mahmood, Kutub
Highlights: Immunogenicity and efficacy of the MDCK- and egg-based LAIV against viruses of H5 and H7 subtypes was studied in ferrets. Immunogenicity of the MDCK-based H5 and H7 LAIV was comparable to that of egg-based LAIV. MDCK- and egg-based LAIV completely inhibited influenza virus replication in the lower respiratory tract. Two doses of MDCK-based LAIV protected against challenge with heterologous H5N1 heterologous challenge. Abstract: During a pandemic, the availability of specific pathogen free chicken eggs is a major bottleneck for up-scaling response to the demand for influenza vaccine. This has led us to explore the use of Madin-Darby Canine Kidney (MDCK) cells for the manufacture of live attenuated influenza vaccine (LAIV) that provides production flexibility and speed. The present study reports the comparison of the immunogenicity and efficacy of two MDCK-based LAIVs against two egg-based LAIVs prepared from the same pandemic potential strains of H5 and H7 subtypes after a single dose of the vaccine followed by a challenge with a homologous wild type strain. The vaccine strains have been generated by classical method of reassortment using the A/Leningrad/134/17/57 master donor strain. Additionally, a prime-boost regimen of the MDCK-based vaccine followed by a challenge with a homologous wild type strain for H5 and H7 immunized ferrets and also a heterologous wild type strain for the H5 immunized animals was studied. No difference in the hemagglutination inhibition and virus neutralization antibody titers against the homologous virus was observed following a single dose of either egg-based or MDCK-based H5 and H7 LAIV vaccine. A second dose of MDCK-based vaccine significantly boosted antibody titers in the vaccinated animals. Both a single dose or two doses of LAIV provided complete protection from lower respiratory tract infection and resulted in a significant reduction in the virus titers recovered from the throat, nasal turbinates and lungs after challenge with the homologous wild type strain. Protection from a challenge with a heterologous strain of H5 was also observed after two doses of the MDCK-based LAIVs. This data strongly supports the use of MDCK as a substrate for the manufacture of LAIV which ensures reliable quality, safety, production flexibility, speed and breadth of protection, features that are highly critical during a pandemic.